Enhancing Automation with AI-Driven Data Engineering: Bridging the Gap for Future Innovations (International Journal of Engineering and Computer Science, 2020)
Recent developments associated with the introduction of AI in data engineering are particularly significant for automating various data management operations. In today’s industries many businesses produce increasing amounts of data, AI automation enables effective solutions to refine intricate tasks like data preprocessing, detection of anomalies, and predictive modeling. This article concentrates on the changes undergone by data engineering with the incorporation of AI in this process and points out that the usage of artificial intelligence also contributes to workflow optimization, error elimination, and decision-making improvement. When the divide of data engineers and current state of AI are joined together, the possibilities for further advances are vast. In an article reviewing case studies, the utility of AI is explored, concentrating on the success displayed in automating data pipelines and the capacity for future innovation that such automation indicates. It also discusses issues associated with the deployment of AI systems among them being high levels of computation and the problem of bias as well as data privacy. Finally, the study intends to help understand how automation in data engineering with the help of AI technologies can recur industries, enhance effectiveness, and comprehensively contribute to the continuous enhancement of data management practices.Key Insights:• Discussing the use of AI in data engineering automation.• Examples of practical use in different industries.• Focusing on such potential and controlling the risks that may occur in the future.